An Initial Study of Cyber Security for Web Services in Malaysian Organizations - Firkhan Ali bin Hamid Ali; M. Khairul Amin M. Sukri; M. Azahari M. Yusof; Moh Norazmi Nordin; Miswan Surip; Mohd Zalisham Jali (Ismail Saritas, 2024)
Indexed by Scopus